Exercise induced hemolysis: Relation between the activity of glucose-6-phosphate dehydrogenase and the magnitude of the hemolysis (2008)
Introduction: Oxidation and hemolysis associated with physical exercise, moderate and severe, have been studied by several investigations, but only in the most recent have been evaluated how the variations of the genetic determined mechanisms for antioxidative enzymatic erytrocytic capacity, contribute to establish different levels of susceptibility to the hemolysis induced trough exercise, however, those studies have mainly been made on non sedentary subjectswith deficiency of enzyme G6PD. Purpose: The objective of this study was to establish if there is either yes or not a relationship between the activity level of erythrocytic activity of the enzyme G6PD and the hemolysis grade, induced by exercise in adult healthy sedentary men and after an experimental bout of moderate exercise pre-exhaustive and equivalent in modality and intensity. Methods: Twenty five men, sedentary and seemingly healthy, were evaluated after an exercise session of 1 hour over a cycloergometer, with 70% of VO2peak previously founded. On the basis of plasmatic Hb, the proportion of hemolysis and haptoglobin consumed, taking in account the variation of plasma haptoglobin and intravascular hemolysis after and at least three hours post-exercise, were calculated. Results: The experimental subjects presented laboratory evidence (free plasma hemoglobin, percentage of hemolysis and haptoglobin) of intravascular hemolysis immediately after and at least past three hours of exercise bouts. Conclusion: The grade of hemolysis had an inversely significative correlation with the G6PD activity and, this intensity had a significative different behaviour below the percentil 40 media founded for G6PD and above of it. Thus, the oxidative hemolytic response in sedentary and healthy individuals who had lowerlevels G6PD activity with one bout of exercise with 70% of VO2peak was highly variable. © 2008 Corporación Editora Médica del Valle.